Palm Frond Waste as a Carbon Source in the Synthesis of CaO/Biochar Catalysts for the Biodiesel Production Process - Helwani, Zuchra; Amraini, Said Zul; Asmura, Jecky; Siregar, Thasya Nurfadillah; Triwahyuni, Vanny Efia; Abd , Ammar Ali (Heca Journal of Applied Sciences, 2023)
This study aims to synthesize and determine the characterization of activated CaO/Biochar and identify the effect of the mass ratio of CaO/Biochar and KOH concentration on the activity of CaO/Biochar catalysts for the synthesis of CPO-based biodiesel. CaO was obtained from eggshell waste. Biochar is obtained from palm fronds through a torrefaction process. CaO/Biochar catalyst was synthesized by impregnation process using KOH solution. The biodiesel transesterification process using CaO/Biochar catalysts. XRD analysis results obtained CaO and Ca(OH)2 compounds in the catalyst, and the basicity value of the catalyst was >9.3. The best catalytic activity of the CaO/biochar catalyst was obtained at a mass ratio of 12:10 and a concentration of 20% KOH catalyst, with a biodiesel yield of 75.1%.